PENGARUH WAKTU KRISTALISASI DAN TEMPERATUR PEMERAMAN TERHADAP KARAKTER ANALCIM YANG DISINTESIS DARI LUMPUR LAPINDO DENGAN TEKNIK FUSI DAN HIDROTERMAL - , HURUL AINI AS SILMI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The effect of variations in silica sources and reaction conditions on the characteristics of synthesized analcime has been studied. Variations in reaction condition in the scope of this study were aging time, and cristalisation time, while the silica sources used were sodium silicate synthetic (SiO 2 26.5% (w/w)) and sodium silicates extracted from Lapindo mud. Silicates from Lapindo mud were extracted via reflux with 6 M NaOH for 6 h and the filtrate were analysed using X-ray Fluorescence (XRF). The synthesis steps of analcime were divided into two steps, the pre-treatment step and the synthesis step. The pre-treatment step consists of treating Lapindo mud with 6 M HCl under 1 and 6 h, treated Lapindo mud was then labeled as analcime precursor and was then fused with NaOH at molar ratio of NaOH/mud of 1.2. The synthesis steps were carried out as follows: fused precursor was reacted with water under hydrothermal condition without using any organic templates with initial molar ratio of 3.6 Na2O : Al2O3 : 5.7 SiO2 . In addition, silicates from various source was added into the system prior the hydrothermal reaction to study the effects on the properties of synthesized analcime. Analcime was then characterized by infrared (IR) spectroscopy, X-ray Diffraction (XRD), and XRF. Analcime with the highest crystallinity was then analysed for its morphology and chemical composition with scanning electron microscope-energy dispersive X-ray (SEM-EDS) apparatus. The results showed that acid-treatment increased the Si/Al ratio of analcime from 2.96 to 5.02 and 6.37 after acid treatment for 1 and 6 h respectively. Metal impurities were also found to be decreased by acid treatment of Lapindo mud. Silicate extracted from Lapindo mud had a SiO 2 content of 44% (w/w). Analcime with the highest Si/Al ratio was obtained under aging temperature at 50 o C (Sa-50) and crystallisation time at 24 hour (Tk-24). Silicate addition during hydrothermal process increased the crystallinity and improved the morphology of analcime product, but decreased its Si/Al ratio. Analcime particle size varied from 4.3-6.5 Âµm and has a trapezohedron morphology.